THE EFFORTS OF THE HEADMASTER IN IMPROVING THE ABILITY OF TEACHERS TO MANAGE THE LEARNING PROCESS THROUGH THE IMPLEMENTATION OF CLINICAL SUPERVISION IN SDN WONOREJO V/316 SURABAYA - Siatun Siatun (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Clinical supervision is a process of guidance in education that aims to assist the professional development of teachers in teaching introduction through observation and analysis of the data objectively, thoroughly, as a basis for transforming teaching behavior. In such position, the researcher aspires to conduct a class action research entitled "Principal's Efforts to Improve Teachers' Ability to Manage the Learning Process through the Implementation of Clinical Supervision at SDN Wonorejo V / 316 Surabaya”.